2022
DOI: 10.3390/jcm11175052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Outcomes of Titanium and Zirconia Implant Abutments: A Systematic Review of Systematic Reviews

Abstract: Background: Dental implants are widely used and in order to answer to esthetic demands, zirconia has been introduced as an abutment material as an alternative to titanium. Several studies have been published on this topic, but the results have been often inconsistent. The objective of the present study is to systematically analyze the existing literature comparing clinical outcomes of titanium and zirconia implant abutments. The study was designed as a systematic review of systematic reviews. Methods: This sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The lower fracture rate in Group 2 may be attributed, to a large extent, to the ductility of the titanium base, which provides higher resistance to chewing force and allows for some deformation when exposed to unfavorable movements. This finding is consistent with previous systematic reviews, which reported zirconia abutment fracture rates varying from 1.08% to 17.86% depending on age, sex, abutment and implant systems, and implant-abutment connections (Gou et al, 2019;Halim et al, 2022). The present study similarly found that more fractures were observed in young male patients compared to females (37.50% vs. 0%, p = .029).…”
Section: Ta B L Esupporting
confidence: 93%
See 1 more Smart Citation
“…The lower fracture rate in Group 2 may be attributed, to a large extent, to the ductility of the titanium base, which provides higher resistance to chewing force and allows for some deformation when exposed to unfavorable movements. This finding is consistent with previous systematic reviews, which reported zirconia abutment fracture rates varying from 1.08% to 17.86% depending on age, sex, abutment and implant systems, and implant-abutment connections (Gou et al, 2019;Halim et al, 2022). The present study similarly found that more fractures were observed in young male patients compared to females (37.50% vs. 0%, p = .029).…”
Section: Ta B L Esupporting
confidence: 93%
“…The titanium abutment has long been considered the gold standard for implant restoration longevity due to its high mechanical stability and excellent biocompatibility (Halim et al, 2022; Sailer et al, 2009). However, as dental technology and materials continue to advance, metal‐free treatment options are becoming increasingly popular in the field of dentistry due to their advantages over traditional metal‐based treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis on the difference between titanium and zirconia abutments under mechanical, biological and aesthetic aspects has not been statistically significant (Halim et al, 2022). The previously reported high short‐term survival rate of 97.6% for monolithic and veneered single implant prosthesis (Pjetursson et al, 2021) was affirmed by this present systematic review.…”
Section: Discussionmentioning
confidence: 97%
“…This problem of not taking into considerations problems that might have occurred over time with the abutment/reconstruction has also been reported in other systematic reviews (Pjetursson et al, 2018). And it is common knowledge that survival does not equal a successful treatment (Halim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%